IDENTIFIKASI UNSUR-UNSUR PEMBENTUK KARAKTER ARSITEKTURAL BANGUNAN GEREJA KRISTEN JAWA KLASIS YOGYAKARTA UTARA - Kaunang, Alvita Melina Surtania (Universitas Atma Jaya Yogyakarta, 2012)
Abstract: In Indonesia there are several church fellowships. Design of their buildings is influenced by the location, ideology, or ordinances of worship. Synod Javanese Christian Church was first established by local residents since the Dutch colonial period. The synod is divided into 32 clusters based on the distribution area of Java. Each of these clusters is called â€œKlasisâ€, The purpose of this research was to explore elements which are significant to the architectural character of Java Christian Church referring to the implementation of Christian symbols and characteristics of traditional architecture of Javanese on building elements of Java Christian Church in â€œKlasis Yogyakarta Utaraâ€. Research method includes data collection method, data processing method, and the method of making conclusions. The method of data collection consists of literature study, surveyâ€” that includes observation, documentation of the building physical data in the form of sketches of floor plan and building facade, including photographsâ€”, and distributing questionnaires. Methods of processing and analyzing data in the form of questionnaire conducted by tabulating data and calculating the percentage of the dominant variable elements of the building which are considered using Christian symbols and characteristics of traditional Javanese architecture. Meanwhile, sketches of the floor plan and building facade, analyzed by the Ordering Principles stated by Ching (2007). The result indicates that Javanese Christian Church building implements the Christian symbols more significantly rather than characteristics of traditional Javanese architecture. Dominant variables which are applying the Christian symbols are ornaments, windows, and furniture.Keywords: Java Christian Church, architectural character, Christian symbol, traditional architecture of JavaneseAbstrak: Di Indonesia terdapat beberapa persekutuan gereja yang rancangan bangunan gerejanya dipengaruhi oleh faktor lokasi, ideologi, atau tata cara ibadah. Sinode Gereja Kristen Jawa didirikan pertama kali oleh penduduk lokal sejak masa kolonial Belanda. Sinode tersebut terdiri dari 32 Klasis yang terbagi menurut persebaran wilayah di Pulau Jawa. Tujuan penelitian ini adalah untuk menelusuri unsur-unsur pembentuk karakter arsitektural bangunan Gereja Kristen Jawa dengan mengacu pada penerapan simbol Kristiani dan ciri khas arsitektur tradisional Jawa pada unsur-unsur bangunan Gereja Kristen Jawa Klasis Yogyakarta Utara. Metode penelitian yang digunakan, meliputi metode pengumpulan data, pengolahan data, serta penarikan kesimpulan. Metode pengumpulan data dilakukan dengan studi literatur, survei, yang meliputi pengamatan, pendokumentasian data fisik bangunan berupa gambar denah, tampak serta foto, dan menyebarkan kuesioner. Metode pengolahan dan analisis data yang berbentuk kuesioner dilakukan dengan cara tabulasi data dan menghitung persentase variabel yang dominan dari unsur-unsur bangunan yang dianggap menerapkan simbol Kristiani dan ciri khas arsitektur tradisional Jawa, sedangkan untuk data yang berbentuk sketsa, yaitu denah dan tampak, dianalisis dengan prinsip penataan Ching (2007). Hasil penelitian menunjukkan bahwa bangunan Gereja Kristen Jawa secara signifikan lebih menerapkan simbol Kristiani dibandingkan dengan menerapkan ciri khas arsitektur tradisional Jawa. Variabel yang dominan menerapkan simbol Kristiani adalah ornamen/ragam hias, jendela, dan perabotan.Kata kunci: Gereja Kristen Jawa, karakter arsitektural, simbol Kristiani, arsitektural tradisional Jawa